Drivers and policy insights for enhancing blue carbon cooperation mechanism between China and ASEAN countries - Lei Zhang (Frontiers in Marine Science)
China and most of the Association of Southeast Asian Nations (ASEAN) countries locate around the South China Sea (SCS), which is home to an abundance of blue carbon resources including mangroves, seagrasses, and saltmarshes. Establishing a blue carbon cooperation mechanism between China and ASEAN countries will contribute greatly addressing climate change and sustainable development in the SCS region. As the climate change impacts, and both China and ASEAN countries have the demand for low carbon development needs, it is necessary for them to cooperate on blue carbon management. By providing a clear picture of the processes and challenges of blue carbon cooperation between China and ASEAN countries in the SCS region, this paper identifies opportunities for countries to develop blue carbon to reduce climate change pressures and support the long-term well-being of coastal communities, and explores new paths for blue carbon protection based on existing maritime cooperation, outlining cooperation policy options that China and ASEAN countries in the SCS region can consider.